Research on Ultimate Bearing Capacity of Angular Contact Ball Bearings Considering Misalignment Angles - Wang Huijie; Qiu Ming; Li Junxing; Liu Zhiwei; Yang Chuanmeng (Jixie chuandong)
Considering misalignment angles will appear during the actual installation of angular contact ball bearings and truncated contact ellipse will be produced due to bearing excessive external load, a bearing limit bearing capacity analysis model containing misalignment angle is put forward. By improving the algorithm, the number of equations and the difficulty of solving the model are reduced. Then the correctness of the algorithm is verified by comparing it with literature and Romax software. Finally, the angular contact ball bearing 7008C is taken as the research object and the influence of different parameters on the ultimate load carrying capacity is analyzed. The results show that increasing the misalignment angle and radial force, increasing the number of rolling elements, and reducing the diameter of rolling elements will weaken the ultimate axial force and the ultimate overturning moment to a certain extent, and increasing the curvature radius coefficient and shoulder height can significantly improve the ultimate axial force and the ultimate overturning moment. However, the minimum shoulder height restricts the bearing ultimate load carrying capacity.